Considering Dawam Raharjo as the Foundation of Sharia Digital Business Ethics - Azzumi, Aufa Rizka; Aziz, Jamal Abdul (Money: Journal of Financial and Islamic Banking, 2023)
Purpose - This research aims to investigate the application of ethics in Sharia digital business and its potential impact on consumer trust and satisfaction in the context of Islamic fintech. The rapid expansion of Sharia fintech has led to the need for strong business ethics to guide and ensure the provision of quality services in the industry. Islamic business ethics, based on Sharia principles, play a crucial role in maintaining the continuity of Sharia business and promoting healthy competition. Additionally, the study explores the potential of Sharia digital business ethics in empowering society and supporting social empowerment initiatives within the framework of Islamic economics. Method – The research methodology employed in this study is qualitative content analysis, utilizing the works of Dawam Rahardjo as primary data sources. The data collection involves the analysis of written documents, including books authored by Rahardjo. The analysis focuses on identifying the compatibility and relevance between the draft ethical principles proposed by Rahardjo and the applied values in Sharia digital business. The life history approach is also employed to gain insights into Rahardjo's perspectives on business ethics. Result– The literature review examines the perspectives of Dawam Rahardjo, a prominent figure in Islamic economics, on Islamic business ethics. Rahardjo emphasizes the importance of fairness, transparency, responsibility, and accountability in business operations. The concept of "ta'awwun" (cooperation) is also highlighted as a key principle in Islamic economics. The review further discusses the ethical principles and values that underpin Sharia digital business, such as fairness, honesty, transparency, trust, and social responsibility. Jelaskan hasil yang diperoleh dari penelitian ini Originality (Novelty) - This research integrates the perspectives of Dawam Rahardjo, a prominent figure in Islamic economics and business ethics, to provide a comprehensive understanding of the ethical principles that should guide Sharia digital business. By analyzing Rahardjo's works and examining the compatibility and relevance of his ethical framework in the context of Sharia digital business, this research expands on the existing knowledge and offers practical insights for digital companies operating in accordance with Sharia principles. Implications – The findings of this research will contribute to a deeper understanding of the application of ethics in Sharia digital business and its potential effects on consumer trust and satisfaction. The study will provide insights into the importance of ethics in maintaining long-lasting consumer confidence, promoting ethical practices in digital business operations, and empowering society. Moreover, the research will offer guidelines and recommendations for sharia-compliant digital companies to establish a loyal customer base and contribute to social well-being.